Quasi‐linear simulations of inner radiation belt electron pitch angle and energy distributions. Issue 6 (24th March 2016) - Albert, Jay M.; Starks, Michael J.; Horne, Richard B.; Meredith, Nigel P.; Glauert, Sarah A.
Abstract: "Peculiar" or "butterfly" electron pitch angle distributions (PADs), with minima near 90°, have recently been observed in the inner radiation belt. These electrons are traditionally treated by pure pitch angle diffusion, driven by plasmaspheric hiss, lightning‐generated whistlers, and VLF transmitter signals. Since this leads to monotonic PADs, energy diffusion by magnetosonic waves has been proposed to account for the observations. We show that the observed PADs arise readily from two‐dimensional diffusion at L = 2, with or without magnetosonic waves. It is necessary to include cross diffusion, which accounts for the relationship between pitch angle and energy changes. The distribution of flux with energy is also in good agreement with observations between 200 keV and 1 MeV, dropping to very low levels at higher energy. Thus, at this location radial diffusion may be negligible at subrelativistic as well as ultrarelativistic energy. Key Points: Hiss, lightning‐generated whistlers, and VLF transmitters can cause butterfly distributions at L = 2 Cross diffusion and boundary conditions must be treated properly to reproduce the distributions The butterfly distributions may be enhanced by magnetosonic waves